2022
DOI: 10.1088/1361-6455/ac489d
|View full text |Cite
|
Sign up to set email alerts
|

UV-induced dissociation of CH2BrI probed by intense femtosecond XUV pulses

Abstract: The ultraviolet (UV)-induced dissociation and photofragmentation of gas-phase CH2BrI molecules induced by intense femtosecond extreme ultraviolet (XUV) pulses at three different photon energies are studied by multi-mass ion imaging. Using a UV-pump — XUV-probe scheme, charge transfer between highly charged iodine ions and neutral CH2Br radicals produced by C—I bond cleavage is investigated. In earlier charge-transfer studies, the center of mass of the molecules was located along the axis of the bond cleaved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
3
5
0
Order By: Relevance
“…The present study is as an extension of a previous publication, 21 where the photodissociation of bromoiodomethane was investigated around the maximum of the first two absorption bands, the A and A′ bands, at 266 and 210 nm, respectively. In a similar fashion than that of the present work, the formation of the I( 2 P 3/2 ), I*( 2 P 1/2 ), Br( 2 P 3/2 ), and Br*( 2 P 1/2 ) photoproducts was experimentally characterized by using the VMI and slice imaging (SI) techniques and 22 which was very much in agreement with the conclusions found by Kockert et al 18 The region of the VUV absorption spectrum of CH 2 BrI in which the present work focuses has not received as much attention as the A and A′ bands. As introduced in the previous paragraphs, only Butler et al 8 studied thoroughly the photodissociation of the title molecule at 193 nm using photofragment translational spectroscopy.…”
Section: ■ Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present study is as an extension of a previous publication, 21 where the photodissociation of bromoiodomethane was investigated around the maximum of the first two absorption bands, the A and A′ bands, at 266 and 210 nm, respectively. In a similar fashion than that of the present work, the formation of the I( 2 P 3/2 ), I*( 2 P 1/2 ), Br( 2 P 3/2 ), and Br*( 2 P 1/2 ) photoproducts was experimentally characterized by using the VMI and slice imaging (SI) techniques and 22 which was very much in agreement with the conclusions found by Kockert et al 18 The region of the VUV absorption spectrum of CH 2 BrI in which the present work focuses has not received as much attention as the A and A′ bands. As introduced in the previous paragraphs, only Butler et al 8 studied thoroughly the photodissociation of the title molecule at 193 nm using photofragment translational spectroscopy.…”
Section: ■ Introductionsupporting
confidence: 92%
“…The main finding of this work was an anchor effect due to the substituent Br atom in the parent molecule, which implies significant rotational motion of the dissociating molecule, and leads to a remarkable rotational energy of the CH 2 Br radical cofragment. It was concluded that this energy flux into internal degrees of freedom of the molecule is the main key factor governing the real time photodissociation dynamics, 22 which was very much in agreement with the conclusions found by Kockert et al 18 The region of the VUV absorption spectrum of CH 2 BrI in which the present work focuses has not received as much attention as the A and A′ bands. As introduced in the previous paragraphs, only Butler et al 8 studied thoroughly the photodissociation of the title molecule at 193 nm using photofragment translational spectroscopy.…”
Section: ■ Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…From the fundamental point of view, tracking photoinduced molecular dynamics allows stringent tests of quantum chemistry models over a broad range of conditions. Such experimental studies, many of which have been performed at synchrotron radiation sources, have gained momentum in the past decade owing to the new possibilities offered by free electron laser (FEL) radiation sources, 1–7 high-order harmonic generation (HHG) 8–15 and the development of various time-resolved techniques. 8,16–19 Consequently, there is a wealth of new information on time evolution of photoinduced molecular dynamics in small quantum systems.…”
Section: Introductionmentioning
confidence: 99%